Risk factors of abnormal uterine activity - L. N. Petrich; O. N. Novikova (Фундаментальная и клиническая медицина)
Aim. To identify risk factors for abnormal uterine activity.Materials and Methods. We recruited 200 pregnant women who delivered in the Maternity Hospital of the Podgorbunskiy Regional Clinical Emergency Hospital from 2018 to 2019, evaluating course of pregnancy and labor activity. Patients were further stratified into those who delivered at term (n = 100) but had abnormal uterine activity and those with urgent delivery (n = 100).Results. The most significant risk factors for abnormal uterine activity were smoking (OR = 26.9, 95% CI = 9.1-79.6), lack of prenatal care visits (OR=16,882, 95% CI = 7.3-39.2), common-law marriage (OR = 5.4, 95% CI = 2.3-12.5), low socioeconomic status (OR = 2.5, 95% CI = 1.3-4.6), higher education (OR = 4.5, 95% CI = 2.5-8.2), and age > 30 years (OR = 3.6, 95% CI = 1.0-13.5). Patients with abnormal uterine activity more frequently suffered from dysmenorrhea, cervical pathology (OR = 1.8, 95% CI = 0.9-3.7), anemia (OR = 1.7, 95% CI = 0.9-3.1), and obesity (OR=2.6, 95% CI = 1.2-5.5). The leading factors associated with abnormal uterine activity are normal birth canal and fetoplacental unit as well as proper cervical ripening.Conclusions. Psychophysiological alterations represent a major risk factor for abnormal uterine activity, contributing to placental insufficiency, fetal growth restriction, and premature rupture of membranes. Procedures aimed at cervical ripening may reduce the incidence of abnormal uterine activity and improve both maternal and newborn outcomes.